Association of Retained Fetal Membranes with Haematological Profile in Crossbred Cows - Rokde, K.; Kumar, S.; Bhardwaz, A.; Mahour, S.S.; Nema, S.P.; Aich , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
This study was carried out on clinical cases of retained fetal membranes in crossbred cows presented at College Clinics and College dairy farm and from Villages in and around Mhow. The blood samples were collected from jugular vein just before 12 hr. postpartum and on 7th day postpartum. Haematological profile revealed that the mean values of haemoglobin, neutrophil and monocyte count after 12 hrs and 7th day postpartum were significantly lower and lymphocyte count was significantly higher in RFM cows (n=18) than normally calved cows (n=6). The differences in mean TLC, eosinophil and basophil counts were non-significant at 12 hrs postpartum, however on 7th day postpartum the TLC and eosinophil count were significantly higher and basophil count was non-significantly different in RFM cows than the normally calved cows.